Perlindungan Data Pribadi Konsumen Oleh Penyelenggara Sistem Elektronik Dalam Transaksi Digital - Rista Maharani; Andria Luhur Prakoso (Jurnal USM Law Review)
This research explores the obligations of Electronic System Providers in protecting the personal data of consumers in electronic services during digital transactions in e-commerce, particularly in the applications Akulaku, Lazada, and Tokopedia. In the field of digital economic transactions, the significance of personal data is increasing, driven by the widespread use of big data. Although the digital economy undoubtedly contributes to overall economic growth, consumer data protection is still inadequately addressed, leading to concerns about numerous data breach cases. This research analyzes the extent to which these three platforms fulfill their legal obligations. The issues are examined through the lens of legal certainty, utilizing a normative juridical method focused on the analysis of legislation, legal norms, and often-used legal principles. Compliance of electronic service providers is reflected in the privacy policies and usage regulations implemented by each platform. Additionally, non-compliance with these obligations results in administrative sanctions. Proactive efforts such as improving security systems, community training, and the involvement of certification institutions are also focal points in minimizing the risks of data breaches. It is crucial to continually monitor the developments in data protection practices on these platforms, given their dynamic nature, and ensure that regulations and policies remain up-to-date. Thus, the results of this research provide insights into the extent to which e-commerce electronic service providers have fulfilled their obligations in protecting consumer personal data.